A “Hijacked Salaried Status” in French Cooperatives of Freelance Workers: The Political Meaning of Shifts Between Standard and Non-standard Employment - Bajard, Flora (Frontiers in Sociology, 2020)
This article considers a specific sub-type of non-standard employment—self-employment—through a particular type of cooperative in France: the Business and Employment Cooperatives (BEC), i.e. collectives of freelance workers. BECs aim to provide an indefinite employment contract—and the social protection associated with it—to these individuals who therefore become “salaried entrepreneurs.” To better understand the gray zones of work, where legal status, practices and identities are often disconnected, this inquiry is based on a qualitative approach to social actors’ practices. It shows, on a meso level, how BECs “hijack” the standard wage-labor contract on the grounds that this is emancipatory and therefore drag it into a non-standard form of employment. In addition with this first shift between the legal framework and its interpretation, a second shift occurs as each member of the cooperative—a “false wage earner”—develops a singular relationship to the constraints related to such a contract. Through the notion of “praxis,” combining both objective and subjective dimensions of work, we are able to systematize the analysis of qualitative data and identify the factors that influence such a diversity of appropriations: the relationship to conflictuality and political competence. Finally, this article highlights the conditions under which social actors make a wide range of appropriations of common legal frameworks, whose flexibility requires us to consider employment relationships as variant and creative practices rather than as “perfect” or “deviant” forms.